Improving Students’ Speaking Skill Through ESA Straight for Word Model At The Year 11th Students Of MA MUHAMMADIAH 1 MALANG - abdul azis (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: In this research, the researcher found some problems at the year 11th Students of MA MUHAMMADIAH 1 MALANG   in speaking. Student’s problem in speaking was difficulty to put passive voice into their conversation. The cause of student’s difficulty were low in motivation, got difficulties to deliver what they want to say because they did not have an idea to speak, and they were afraid of making a mistaketo make an error. This situation made the students inactive and not enthusiastic in learning speaking in class.From the preliminary study, the researcher found that the total score of the students were 58,95. From all the students, 85% of them dominated the low score. Besides, the students who have high level in English speaking were 14% students. While, the expected score on the school basis of the Minimum Mastery Learning (KKM) standard is 75. Based on the result above, the ability of students’ speaking skill needs to be improved. ESA straight for word was an appropriate method to solve the problem. This first type of ESA prepared a chance to the students to practice their speaking skill.The researcher used Classroom Action Research as the research design. The subject of this study was at the year 11th Students of MA MUHAMMADIAH 1 MALANG   which consists of 21 students. The procedure of the research consisted of some main steps: planning the action, implementation, observation (collecting the data), and reflection. The data were analyzed quantitatively. The quantitative data were obtained from the test.The findings of the research showed that ESA straight for word can improve students’ speaking ability. The result of the test showed that 76% of the students got score ≥75 in which the mean score was 78.61. Finally, considering the findings above, this study had reached the expected outcome and the criteria of success. Hence the study was only conducted in one cycle.Based on the result of the study, the English teacher is suggested to apply ESA straight for word as method in teaching speaking. It can solve the students’ problems in speaking as like the year 11th students of MA MUHAMMADIAH 1 MALANG which were difficulty to put passive voice into their conversation. It is also suggested for the future researchers that the use of ESA straight for word as method in teaching speaking is needed to be explored further in different grades, levels of education, and different skills. Keywords: Speaking skill, ESA (engage, study, activate), and ESA straight for word model.